2012
DOI: 10.1088/1757-899x/27/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of the formation of primary intermetallics under ultrasonic melt treatment in an Al-Zr-Ti alloy

Abstract: Ultrasonic melt treatment (UST) is known to induce grain refinement in aluminum alloys, especially when transition metals like Zr and Ti are present. The refinement of primary intermetallics (e.g. Al 3 Zr, Al 3 (Zr,Ti)) caused by UST may influence the subsequent solidification process when intermetallics act as nucleation sites. In this paper, an Al-Ti-Zr alloy is used to analyse the effect of different ultrasonic intensities on the formation of these primary intermetallics. The possible nucleation behaviour o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
3
4
0
Order By: Relevance
“…3c and d may suggest that some of the Al 3 Zr plates fragmented by cavitation may be fused with other fragments at the matching facet surface upon their travel in the melt due to the low melt temperature. The clustering or agglomeration of Al 3 Zr resembles the microstructure observed by Zhang et al 31 In their work, such Al 3 Zr agglomeration was typically found when a lower UST power was employed. This agglomeration was not observed anymore when the UST power was increased.…”
Section: Discussionsupporting
confidence: 71%
“…3c and d may suggest that some of the Al 3 Zr plates fragmented by cavitation may be fused with other fragments at the matching facet surface upon their travel in the melt due to the low melt temperature. The clustering or agglomeration of Al 3 Zr resembles the microstructure observed by Zhang et al 31 In their work, such Al 3 Zr agglomeration was typically found when a lower UST power was employed. This agglomeration was not observed anymore when the UST power was increased.…”
Section: Discussionsupporting
confidence: 71%
“…% leads to the formation of primary Al 3 Zr particles in the as-cast structure and negatively affects the properties of the investigated alloys. The same results are reported in [21][22][23]. Furthermore, the appearance of the primary Al 3 Zr can also be associated with such disadvantages of the alloy production regime as casting temperature and cooling rate.…”
Section: Discussionsupporting
confidence: 79%
“…According to Equation (1), the strengthening effect from the metastable nanoscale Al 3 Zr L1 2 dispersoids with an average size of 10 nm was 17-times higher compared to the stable incoherent plate-like D0 23 Al 3 Zr particles with a length equal to 200 nm and a thickness of about 50 nm ( Figure 6). Kendig et al also reported that the maximum hardening is achieved with the size of precipitates Al 3 Zr at 5-10 nm [26].…”
Section: Discussionmentioning
confidence: 99%
“…High frequency and high amplitude oscillations result in cavitation of the melt and also promote intense mixing through agitation [10,11]. The reported mechanisms are related either to increasing the number of nucleation sites or to improving the nucleant potency of the particles [10][11][12][13][14][15]. Our previous results show that when transition metals Zr and Ti are present in the melt, UST becomes very efficient for grain refinement in aluminum alloys, especially when it is performed in the temperature range of primary solidification of Al 3 Zr [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The reported mechanisms are related either to increasing the number of nucleation sites or to improving the nucleant potency of the particles [10][11][12][13][14][15]. Our previous results show that when transition metals Zr and Ti are present in the melt, UST becomes very efficient for grain refinement in aluminum alloys, especially when it is performed in the temperature range of primary solidification of Al 3 Zr [12][13][14][15]. The ultrasonicaided grain refinement in the alloys containing Zr and Ti was related to the refinement of primary Al 3 (Zr,Ti) intermetallics upon cavitation, significant increase of their number and further involvement in solidification as nucleation sites for aluminum.…”
Section: Introductionmentioning
confidence: 99%